2016
DOI: 10.1371/journal.pone.0156174
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Terminally Ill Patients in End of Life Talk: How Experienced Palliative Medicine Doctors Navigate the Dilemma of Promoting Discussions about Dying

Abstract: ObjectiveTo examine how palliative medicine doctors engage patients in end-of-life (hereon, EoL) talk. To examine whether the practice of “eliciting and responding to cues”, which has been widely advocated in the EoL care literature, promotes EoL talk.DesignConversation analysis of video- and audio-recorded consultations.ParticipantsUnselected terminally ill patients and their companions in consultation with experienced palliative medicine doctors.SettingOutpatient clinic, day therapy clinic, and inpatient uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…36 Also, by first soliciting a patient or family member's perspective, the clinician can then take the patient's or family member's perspective into account when providing their own perspective. 34,63 How clinicians, patients, and family members refer indirectly to the future There are a diverse range of practices that can be used to more or less indirectly refer to illness progression or end of life. The most indirect practices included clinicians alluding to the likelihood of illness progression, such as by stating that current treatment has been exhausted: "I think we've gotten as much as we're going to get from this treatment."…”
Section: How Clinicians Provide Opportunities For Patients or Family mentioning
confidence: 99%
See 3 more Smart Citations
“…36 Also, by first soliciting a patient or family member's perspective, the clinician can then take the patient's or family member's perspective into account when providing their own perspective. 34,63 How clinicians, patients, and family members refer indirectly to the future There are a diverse range of practices that can be used to more or less indirectly refer to illness progression or end of life. The most indirect practices included clinicians alluding to the likelihood of illness progression, such as by stating that current treatment has been exhausted: "I think we've gotten as much as we're going to get from this treatment."…”
Section: How Clinicians Provide Opportunities For Patients or Family mentioning
confidence: 99%
“…This is particularly the case when the person being discussed is either involved in the conversation or is a significant for one or more parties to the conversation. 28,32,34,41 How clinicians, patients, and family members refer explicitly to the future In contrast to practices that discuss future deterioration and end of life indirectly, these studies explore instances where such matters are made explicit. On some occasions, discussions about end of life were initiated by clinicians indirectly, and subsequently made explicit by patients.…”
Section: How Clinicians Provide Opportunities For Patients or Family mentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacists will need to develop strategies that enable them to deal with these discussions. As recent research has shown, this requires skilful techniques that rely on the patient's use of verbal or non-verbal cues in order to explore the concerns of patients, their relatives or carers in ways that allow patients to raise EoL considerations when they are ready [16] . Where patients wish to nominate a relative or carer to have these discussions, it is important to support their wishes and establish their consent.…”
Section: Explaining Clinical Options and Risks And Benefitsmentioning
confidence: 99%